2019
DOI: 10.3329/imcjms.v13i1.42050
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of implicit bias in health care: A call for intersectionality

Abstract: Background and objectives: Health disparities are a growing concern in health care. Research provides ample evidence of bias in patient care and mistrust between patient and providers in ways that could perpetuate health care disparities. This study aimed to review existing literature on implicit bias (or unconscious bias) in healthcare settings and determine studies that have considered adverse effects of bias of more than one domain of social identity (e.g., race and gender bias) in health care. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Race was not a predictor in the current study; however, this intersection was significant in the early study by Boysen and Vogel (2008), which found a positive correlation between negative implicit bias toward African Americans and LG persons. Though implicit racial bias has been studied (Kruse et al, 2022), the intersection of race and implicit bias toward LG persons is understudied (Ogungbe et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Race was not a predictor in the current study; however, this intersection was significant in the early study by Boysen and Vogel (2008), which found a positive correlation between negative implicit bias toward African Americans and LG persons. Though implicit racial bias has been studied (Kruse et al, 2022), the intersection of race and implicit bias toward LG persons is understudied (Ogungbe et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Efforts toward this goal will be most successful if interdisciplinary teams of health informatic specialists, behavioral scientists, clinicians, and health services researchers lead this work. Expanded use of intersectionality as an analytic tool is also needed to accurately characterize how biases interlock and identify the object of detected biases (Ogungbe et al, 2019). Health systems must be responsive to this work by investing in patient centered EHR systems and routine workplace trainings to reduce provider bias.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we assessed perceived discrimination using a measure that was not specific to the health care setting; thus, one should not assume that all the reported experiences occurred in the context of health care obtained from the VHA or in any other health care setting. Nonetheless, achieving health equity will necessitate that health care systems also address provider-and system-level factors that may contribute to health disparities, such as provider implicit bias and health care-related discrimination (48,49).…”
Section: Discussionmentioning
confidence: 99%